A metagenomic analysis of the modulatory effect of Cyclocarya paliurus flavonoids on the intestinal microbiome in a high‐fat diet‐induced obesity mouse model. (5th March 2019) - Cheng, Lu; Chen, Yuhui; Zhang, Xin; Zheng, Xiaojie; Cao, Jinxuan; Wu, Zufang; Qin, Wenyan; Cheng, Kejun
Abstract: BACKGROUND: As a result of a low bioavailability, the majority of Cyclocarya paliurus flavonoids (CPF) remain in the large intestine where they accumulate to exert a modulatory effect on the intestinal micro‐ecology. Therefore, the present study investigated the modulatory effect of CPF on intestinal microbiota. RESULTS: CPF dramatically ameliorated the obesity‐induced gut dysbiosis. A significant decrease ( P  < 0.05) was observed in the ratio of Firmicutes / Bacteroidetes after CPF treatment for 8 weeks. Moreover, Kyoto Encyclopedia of Genes and Genomes pathways of biosynthesis of amino acids, the two‐component system and ATP‐binding cassette transporters enriched the most differentially expressed genes after CPF intervention. CONCLUSION: The results of the present study indicate that CPF might have prebiotic‐like activity and could be used as a functional food component with potential therapeutic utility to prevent obesity‐related metabolic disorders by manipulating the gut flora and affecting certain metabolic pathways, thus contributing to the improvement of human health. © 2019 Society of Chemical Industry